Problematika Remaja Di Era Digital: Sebuah Pendekatan Psikologi Komunikasi - Abdul Hadi; Lilik Sumarni (Universitas Katolik Widya Karya Malang, 2023)
Youth is the future asset of a nation. But nowadays a lot is happening to teenagers, such as drugs and motorcycle gangs. This is a familiar problem. Juvenile delinquency includes all behaviors that deviate from the norms of criminal law committed by juveniles. There are so many internal and external factors that cause juvenile delinquency that need to be considered. To overcome this, guidance from parents and also a good environment can be a determinant for the development of the teenager. Based on the results of several studies, it was found that one of the causes of juvenile delinquency is the lack of functioning of the role of parents as role models for their children. The atmosphere in the family that causes discomfort for children is also one of the causes, including the divorce of their parents. Often they commit crimes because they feel they are not cared for by their parents who work too often without paying attention to the child's development. Teenagers who commit crimes generally lack self-control, or actually abuse that self-control, and like to enforce their own rules without paying attention to the presence of other people around them.